Analisis Budaya Patriarki Terhadap Partisipasi Pendidikan Perempuan di Desa Rembitan - Zilly Arsyika Masyhuri; Syafruddin Syafruddin; Nursaptini Nursaptini (LPPM IAIN Parepare, 2025)
Patriarchal culture remains a significant issue in Indonesia, influencing various aspects of social life, including education. The patriarchal value system that positions men as dominant decision-makers has created gender disparities that restrict women’s access to education. This study aims to identify, understand, and analyze the influence of patriarchal culture on women’s educational participation in Rembitan Village, Central Lombok Regency. Using a qualitative case study design, data were collected through in-depth interviews with ten informants and nine female participants who had dropped out of school or had not pursued higher education. The data were analyzed using qualitative techniques and validated through source, method, and time triangulation. The findings reveal that patriarchal values remain deeply rooted in Rembitan society and manifest in two primary forms: (1) cultural patriarchy, which prioritizes boys’ education and reinforces male dominance in decision-making, and (2) domestic patriarchy, characterized by gender-based divisions of labor and male control over household decisions. These conditions limit girls’ motivation and opportunities to pursue education. The study recommends strengthening gender awareness through family and community education, enhancing the role of institutions in promoting equality, and developing local policies that support women’s access to education, particularly in rural areas.